Influence of Seed Fortification Treatment with Inorganic Nutrients and Growth Regulators on Seed and Seedling Quality Characteristics in Bamboo (Bambusa bambosa) - Krishnaveni, K.; Sekar, I.; Rajan, P. Arul; Govinda Rao, M. (Indian Forester, 2010)
The best graded seeds (big and medium sized) were fortified with inorganic nutrients viz., Na2HPO4, K2HPO4, KCI, KNO3, CuSo4, K2So4, ZnSo4 and with water soaking in two different concentration viz., one and two percent, respectively for 24 hours. Among the nutrients, seeds fortified with 1% KNO3 recorded the maximum germination percentage (82%) and vigour index (1092) than control which recorded 53% germination and 345 vigour index respectively. Significantly the highest nursery establishment after 21 days enhanced the germination by 42%. Similarly the same seeds subjected to seed fortification with growth regulators like IBA, BA and GA3 and kinetin with 100 and 200 ppm concentration for 24 hours enhanced the germination and seedling emergence. Seed fortified with 100 ppm GA3 recorded 34 % increases in germination than the control at laboratory. Similarly the nursery establishment of seedlings after 21 days recorded maximum germination of 79% with the vigour index of 3771 than the control with 34 % germination and and vigour index, respectively.